Menyebarkan Pesan Harmoni Strategi Konten dan Pemasaran yang Teruji di Era Media Sosial - Aswati, Fitriana; Rezky Kamal , Fadila; Siti Ainun, Rosydiani (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2024)
The Halaqah Damai Community, as a platform for spreading messages of peace and brotherhood, faces the challenge of reaching a broader audience and building a strong online community in the digital era. This research aims to identify effective content development and marketing strategies on social media to achieve these goals. The study employs a qualitative method of audience analysis to understand the characteristics and preferences of the target audience, which is crucial for determining the most relevant and engaging types of content. The findings indicate that the Halaqah Damai Community needs to develop content and marketing strategies focused on creating engaging and beneficial content, along with effective marketing, to build a strong community. This research provides insights into effective content development and marketing strategies on social media for the Halaqah Damai Community. By implementing these strategies, Halaqah Damai can achieve its goals and contribute more significantly to spreading the message of peace.